Project-Based Learning's Impact on Fostering The Socio-Environmental Attitude (International Journal of Environmental Sciences, 2025)
This research aims to reveal the effectiveness of project-based learning on fostering the attitude of students. The research was conducted on a sample of employees of the Department of Curricula and Teaching Methods, after dividing them into two equal groups (control and experimental) at random. To achieve the aim of the current research, a measure of students' attitude towards the course was built. The current research relied on the semi-experimental approach to reveal the relationship between the independent variable and the dependent variable. The results revealed a statistically significant difference among the two research groups in the direction towards the course in favor of the experimental group